Isohypsibius taibaiensis sp. nov. (Tardigrada, Hypsibiidae) from China - Li, Xiaochen; Wang, Lizhi (Zootaxa, 2005)
Isohypsibius taibaiensis sp. nov. differs from the other species of Isohypsibius with three macroplacoids and lunule in having eyespots, accessory points on the principal claws, microplacoid, cuticular bar on claws, relatively short claws, the claws of the 4 th pair of legs not much greater than the others, in lacking cuticular sculpture or rogose cuticle and irregular granules of black or brown pigment on dorsal side.